Post-fire succession - Stančič, Liza (Acta geographica Slovenica, 2018)
Forests in Submediterranean Slovenia are threatened by wildfires every year. The article presents the main characteristics of post-fire regeneration in the Karst area. The rate of succession was studied by comparing two burned sites with different periods after the last fire. Field plant sampling was used to determine the plant cover and species composition on each site. Vegetation characteristics were contrasted with nearby unburned sites. We found that the plant species composition of burned areas is similar to that of areas unaffected by wildfire, and that the monitored site has been colonised by specific pioneer plant species five years after the wildfire.
Keywords: biogeografija; biogeography; gozdni požari; karst; Kras; Slovenia; Slovenija; succession; sukcesija; wildfires